The in vivo studies of injection moulded 316l stainless steel fracture fixation plate - Mohd Jan, Nurul Hafiza; Sha'ban, Munirah; Zulkifly, Ahmad Hafiz; Buyong, Zunariah; Omar, Mohd Afian (2014)
INTRODUCTION: Metal Injection Moulding (MIM) is a revolutionary new class of medical implant fabrication in orthopaedics. This technology employs natural resources and holds great promises in producing large quantities of metallic parts for prosthetic implant at minimum outlay without compromising its quality. MATERIALS AND METHODS: This present study was conducted to compare potential effects of MIM plate for internal fixation in fracture healing in New Zealand White rabbits with conventional machining plate (Synthes®) as control. Following research approval by IIUM Ethics Committee (IIUM/305/20/4/10), forty rabbits were used as model and randomly divided into two groups. All rabbits underwent single transverse mid-shaft tibial fracture surgery and fixation under anaesthesia. The fractures were fixated with either the MIM plate or conventional plate (Synthes®). The monitoring of fracture healing was carried out at week 3, 6, 9, 12 and 26 according to ISO10993-1&2:2006 Standards. The status of bony union was examined by means of plain radiographic assessment, macroscopic observation and, histological evaluation. RESULTS AND DISCUSSION: There were callus formations in both groups. Bony union was starting at week 6 post-operatively, whilst bone remodelling was completed at week 26 with evidenced by plain radiograph assessment followed by macroscopic evaluation. Histological assessment showed that both groups possessed mild to moderate callus bridging at week 3 and week 6, respectively. Complete remodelling of cortical bone was evidenced at week 26. There was no plate broke or bent during the study. CONCLUSION: These findings indicate that the MIM plate has equal potential to hold the fracture as conventional plate. Therefore, locally manufactured the MIM plate is potential to be used as an alternative internal fixator for fracture management in orthopaedic considering conservation value in economic appraisals of natural resources.